Herbal Transformation by Fermentation - Chang-Gue Son; Sam-Keun Lee; In-Kyu Choi; Eun-Su Jang; Kee-Jung Bang (Medical Association of Pharmacopuncture Institute, 2020)
We herein show a dramatic change of herbal properties of the composition as well as function via fermentation of Cynanchi atrati Radix (family Asclepiadaceae). Cynanchi atrati Radix showed a high cytotoxicity against B16-F10 melanoma cell line, but the function of Cynanchi atrati Radix was completely changed into anti-melanin activity at very low concentration after Lactobacillus -fermentation. In addition, the compounds were drastically changed as shown in HPLC-based profile. Furthermore, this transformation has been achieved by only Lactobacillus -fermentation. This study proposes an strategy which we need to consider in the herb-derived material researches including pharmacopuncture.